On the estimation of the rate of convergence in the integrallimit theorem - Banys, J. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. И. Банис. Оценка скорости сходимости в интегральной предельной теоремеJ. Banys. Konvergavimo greičio įvertinimas integralinėje ribinėje teoremoje